(untitled) (Community Based Medical Journal, 2025)
Cigarette smoking is an intractable public health problem that carries threat to the health of entire population. Smoking is a known risk factor for chronic obstructive pulmonary disease, cardiovascular diseases and certain cancers specially lung cancer. This cross-sectional, comparative study was conducted in the outpatient department of Mymensingh Medical College Hospital, Bangladesh, from July 2014 to June 2015, to examine whether the forced expiratory volume in the first second (FEV1) differs between cigarette smokers and non-smokers and also estimate the effect of duration of cigarette smoking on lung function. FEV1 was recorded in total 150 subjects, in which non-smokers were 50 (as control, group I) and numbers of smokers were 100 with duration of smoking was 5-10 years (group IIA) and >10 years (group IIB). FEV1 was measured by using Spiromaster PC-10 Spirometer. A questionnaire including participants’ history and physical examination was completed. FEV1 decreased gradually with the duration of smoking in both study groups i.e., group IIA (5-10 years duration of smoking) and group IIB (>10 years duration of smoking) as compared to the control group (non-smokers, group I) (p<0.001). FEV1 was also found lower in group IIB (>10 years duration of smoking) as compared to group IIA (5-10 years duration of smoking) (p<0.05). Our study showed that cigarette smoking has a strong impact on airway obstruction that is reflected through a reduction in FEV1. CBMJ 2025 January: Vol. 14 No. 01 P:11-15